The Development Of Student Worksheets (LKPD) Based On Indonesian Realistic Mathematics Education (PMRI) On The Material Of Surface Area On Curved Side Of Solid For Students Of SMP Amayatul Huda 2021/2022 Academic Year - Febri Ananda (UMSU, 2022)
This research is a research on the development of Student Worksheets (LKPD) based on Indonesian Realistic Mathematics Education (PMRI) on the subject of curved side space. This study aims to 1) describe the product quality of the Student Worksheet (LKPD) based on Indonesian Realistic Mathematics Education (PMRI) on the subject of curved side space. 2) describe the results of the development of Student Worksheets (LKPD) based on Indonesian Realistic Mathematics Education (PMRI) on the subject of curved side space development. In this study, researchers used research and development procedures according to Sugiyono which have been modified. The subjects of this study were students of class IX SMP Amayatul Huda Kec. Medan, Deli Kel. Labuhan Deli. The object of this research is the Student Worksheet (LKPD) which was developed by the researcher. The data collection technique used is the result of validation and the results of interviews related to student responses regarding the use of the Student Worksheet (LKPD) product. The development procedure in this research includes: (1) Potential and problems; (2) Data collection; (3) Product design; (4) Design validation; (5) Design revision; (6) Product trial. The results of the product validation of the Student Worksheet (LKPD) developed by the researcher were 3.9 and 4.2 and included in the good category. The Student Worksheet (LKPD) developed by the researcher received a positive response from the class IX students of Amayatul Huda Middle School.